2012
DOI: 10.1002/chp.21145
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Interprofessional Education on Collaboration Attitudes, Skills, and Behavior Among Primary Care Professionals

Abstract: A brief IPE program can improve interprofessional attitudes, collaboration skills, and collaborative behavior. That such a program allows professionals to get acquainted with each other and each other's viewpoints appears to be as important as the educational content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 23 publications
(30 reference statements)
7
56
2
Order By: Relevance
“…The updated studies revealed a slightly different situation -while IPE remained voluntary for post-qualification learners (e.g. Robben et al 2012), there was more equality at the undergraduate level, as IPE was either voluntary (e.g. Shiyanbola et al 2014) or compulsory (e.g.…”
Section: Process Factorsmentioning
confidence: 96%
See 2 more Smart Citations
“…The updated studies revealed a slightly different situation -while IPE remained voluntary for post-qualification learners (e.g. Robben et al 2012), there was more equality at the undergraduate level, as IPE was either voluntary (e.g. Shiyanbola et al 2014) or compulsory (e.g.…”
Section: Process Factorsmentioning
confidence: 96%
“…In particular, the updated papers continued to emphasise that the development of IPE was linked to a desire to improve patient care or service delivery through improvement in interprofessional collaboration and teamwork (Carpenter et al 2006;Curran et al 2007;Watts et al 2007;Quinn et al 2008;Fuhrmann et al 2009;Robben et al 2012;Slater et al 2012;Paquette-Warren et al 2014). Again, these drivers were identified as linked to either top-down (e.g.…”
Section: Ipe Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…personcentered care), not as the Illness (the "leg" or "stomach"), which mainly as has been the focus in the divided production-based care of today. This is essential if we will go on improving our service delivery continuously and provide even better, more valuable care in the future [9]. In a longer perspective, collaboration and co-creation would not only improve care and social service, it would also be cost effective [6], since collaboration has shown decreased patients' readmissions to hospital, for example better handover, and readmissions are expensive [10].…”
Section: Short Communicationmentioning
confidence: 99%
“…Because of the volume of the existing literature, we focused on articles describing the benefits and challenges of IPE, individual and organizational barriers to IPE, and faculty development. Researchers have looked at barriers to learning between health and social practitioners (Barr, Hammick, Koppel, & Reeves, 1999;Barrett, Curran, Glynn, & Goodwin, 2007;D'Amour & Oandasan, 2005;Gilbert, 2005b;Robben et al, 2012). Others have examined educators' perceptions of their role adequacy as facilitators of interprofessional learning (Derbyshire, Machin, & Crozier, 2015;Gilbert, 2005a).…”
Section: Introductionmentioning
confidence: 99%